"Inward Growth" Corrosion and Its Growth Mechanism in Ancient Chinese Bronzes. (2020) - Li, Bingjie; Jiang, Xudong; Tu, Yin; Fu, Qiang; Pan, Chunxu
ABSTRACT: We divide the corrosion products on ancient bronzes into two categories, i.e., "inward growth" and "outward growth" corrosions. Several selected Chinese ancient bronzes with the "inward growth" corrosion are studied; and their chemical compositions, microstructures and morphologies are characterized systematically. According to the results, it is found that the "inward growth" corrosion can be further divided into three types, i.e., "noble patina", "noble-like patina" and "lamellar peeling patina". We propose that the growth mechanism of the "inward growth" corrosion is that the corrosion initiates at and develops along α-Cu phase. Furthermore, the effect of alloy Sn content on the "inward growth" corrosion is also studied.